ANALISIS POLA KONSUMSI DAN PENDAPATAN MASYARAKAT DI DESA TANJUNG BELIT KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Butasar, Butasar; Yusuf, Yusbar; Basri, Syafril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to find out how the pattern of consumption and income society that exist in this study unit of analysis is the household in the Village of Tanjung Belit Rambah District Rokan Hulu Regency Year 2018. And used in this study is the primary data that is by providing questionnaires and conduct direct interviews to the sample that has been established namely the head of households in the Village of Tanjung Belit District Rambah Rokan Hulu regency. This research uses descriptive and quantitative methods. Microsoft Excel devices are also used to facilitate the calculation of consumption patterns and community income. The results showed that consumption expenditures and community income are normal, meaning that income and expenditure do not differ much. From the research, it is found that the number of people with high income is 5%, the number of middle income is 25%, and the number of low income society is 75%. It is calculated from the entire sample of respondents that is as many as 40 respondents community. from this study also obtained that total expenditure of respondents as much as Rp 203.100.000 and total income responder of Rp 263.300.000.Keywords : Total Household Expenditure of Respondents and Total Respondents' Household Revenue.